An inverse technique for dielectric-property determination from reflection measurement in spatial domain - Mearnchu, J.; Torrungrueng, D.; Phongcharoenpanich, C.; Krairiksh, M. (My University, 2005)
An inverse technique by reflection measurement in spatial domain is proposed instead of frequency domain. A steepest descent algorithm is used for minimizing performance functions to obtain fast convergence. Comparison results of inverse technique in spatial domain provides good agreement to those obtained from frequency domain ones that shows the possibility to design a low cost dielectric-property determination system. ©2005 IEEE.